2010
DOI: 10.4103/0255-0857.71831
|View full text |Cite
|
Sign up to set email alerts
|

A fatal case of empyema thoracis by Nocardia farcinica in an immunocompromised patient

Abstract: Empyema thoracis by Nocardia farcinica infection is uncommon. Here we report a rare and fatal infection in a 27-year-old HIV- seropositive male who presented with cough, expectoration, and breathlessness. Nocardia farcinica was isolated from sputum and pus from the pleural cavity. Confirmation of the isolate and minimum inhibitory concentrations (MIC) for various antibiotics was done at the Aerobic Actinomycetes Reference Laboratory, Centres for Disease Control and Prevention (CDC), Atlanta. Patient was treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…N. farcinica was of special interest as it is known to be weakly acid-fast positive by ZN staining [36]. Background fluorescence was very low in all samples; this should highly reduce the number of false positive signals in sputum samples, making them easier to read.…”
Section: Methods Optimizationmentioning
confidence: 99%
“…N. farcinica was of special interest as it is known to be weakly acid-fast positive by ZN staining [36]. Background fluorescence was very low in all samples; this should highly reduce the number of false positive signals in sputum samples, making them easier to read.…”
Section: Methods Optimizationmentioning
confidence: 99%
“…In the present study, N cyriacigeorgica was isolated from pulmonary infections in two cases and one disseminated infection in a patient with non-Hodgkin's lymphoma. N farcinica has been reported to be an increasing cause of localized and disseminated infections in immunocompromised patients in recent years (37)(38)(39), but bacteremia remains a rare finding (40,41). In the present study, we reported a case of bacteremia in a 50-year-old woman with breast cancer undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 57%
“…The demographic and clinical characteristics of the patients who presented with nocardial empyema caused by N. farcinica reported in the literature are summarized in Table 1. [14][15][16][17][18][19][20][21][22] A total Graat et al [15] 54 Ohta [19] Severo et al [20] 75/M Community Huang et al [22] 56/M…”
Section: Literature Reviewmentioning
confidence: 99%
“…The demographic and clinical characteristics of the patients who presented with nocardial empyema caused by N. farcinica reported in the literature are summarized in Table 1 [14–22] . A total of 11 patients, including our patient, were identified.…”
Section: Literature Reviewmentioning
confidence: 99%